2021
DOI: 10.3354/esr01155
|View full text |Cite
|
Sign up to set email alerts
|

Warming conditions boost reproductive output for a northern gopher tortoise population

Abstract: The effects of climate change on at-risk species will depend on how life history processes respond to climate and whether the seasonal timing of local climate changes overlaps with species-specific windows of climate sensitivity. For long-lived, iteroparous species like gopher tortoises Gopherus polyphemus, climate likely has a greater influence on reproduction than on adult survival. Our objective was to estimate the timing, magnitude, and direction of climate-driven effects on gopher tortoise reproductive ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…Therefore, a warming climate may make nest incubation conditions more conducive for higher hatching success, potentially leading to larger annual cohorts. Improved reproductive success at the leading edge of geographic ranges with increasing temperatures have been demonstrated for plants (Dangremond & Feller 2016, Ordoñez-Salanueva et al 2021) and invertebrates (Ling et al 2008) and recently observed in gopher tortoises Gopherus polyphemus (Hunter et al 2021). However, warming temperatures could influence hatchling sex ratios, skewing to ward a female bias (Hawkes et al 2007, Reneker & Kamel 2016, Jensen et al 2018, although turtles may compensate by choosing different elevations or digging deeper nests (Hays et al 2001), and temperatures could also be modulated by changes in precipitation and nest moisture (Lolavar & Wyneken 2015).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, a warming climate may make nest incubation conditions more conducive for higher hatching success, potentially leading to larger annual cohorts. Improved reproductive success at the leading edge of geographic ranges with increasing temperatures have been demonstrated for plants (Dangremond & Feller 2016, Ordoñez-Salanueva et al 2021) and invertebrates (Ling et al 2008) and recently observed in gopher tortoises Gopherus polyphemus (Hunter et al 2021). However, warming temperatures could influence hatchling sex ratios, skewing to ward a female bias (Hawkes et al 2007, Reneker & Kamel 2016, Jensen et al 2018, although turtles may compensate by choosing different elevations or digging deeper nests (Hays et al 2001), and temperatures could also be modulated by changes in precipitation and nest moisture (Lolavar & Wyneken 2015).…”
Section: Discussionmentioning
confidence: 94%